Pengaruh Komposisi Medium Tanamdan Konsentrasi Pupuk Organik Cair Limbah Sayur Pasar Terhadap Pertumbuhandan Produksi Sawi (Brassica juncea L.) Sistem Vertikultur - Yohanna Silvia Farina; Ardian Ardian; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the growth and production of mustard using a planting medium composition and concentration of liquid organic fertilizer market vegetable waste with verticulture system. This researsch has been conducted at the Faculty of Agricultural Experimental Station Unit Riau University Campus Bina Widya KM 12,5 Panam Pekanbaru, for 4 months is from April to July 2017. This study used a randomized factorial block design (FBD). The first factor is the composition of the growing medium consisting of 4 levels, top soil: rice husk: sawdust. M0: top soil, M1: 3:2:1, M2: 2:3:2, M3: 1:1:3. The second factor is the concentration of liquid organic fertilizer market vegetable waste which consits of 4 levels, P0:0 ml.liter of water-1, P1: 150 ml.liter of water-1, P2: 300 ml.liter of water-1, P3: 450 ml.liter of water-1.The parameters those observed were: plant height, leaf number, fresh weight, consumable weight, and the root volume. The Ducan’s multiple range test at the 5% level was used for mean separations after analiysis of variance. The composition of embedding medium top soil, rice husk, sawdust (2:3:2) and the concentration of liquid organic fertilizer aste vegetable market of 300 ml.liter of water-1 significantly affected the plant height, leaf number, fresh weight and the root volume.Keywords: mustard, planting medium, liquid organic fertilizer market vegetable waste, verticulture.